Research on the Characteristics of Deformation and Axial Force Changes During Drilling of Thin-Walled AF1410 High-Strength Steel - Yupu Zhang; Shutao Huang; Chengwei Liu; Ruyu Li; Yongshe Sun; Lifu Xu (Applied Sciences)
Axial force and deformation during drilling significantly impact the hole quality of thin-walled high-strength steel components. This study analyzed the drilling process of thin-walled AF1410 steel, focusing on axial force, deformation, drill cap formation, and hole exit edge characteristics. The effects of cutting speed (12.6–37.7 m/min) and feed rate (0.01–0.1 mm/r) were also examined. Initially, the steel plate undergoes elastic, outward bulging deformation. Axial force, driven by elastic resistance, rises from 114.9 N to 322.1 N as feed rate increases from 0.025 mm/r to 0.1 mm/r, with minimal influence from cutting speed. As drilling progresses, axial force increases slowly. Near the hole exit, plastic deformation occurs beneath the drill bit, causing material to yield and form a drill cap. This results in a sharp rise in axial force, with maximum values increasing from 314.2 N to 525.3 N at higher cutting speeds and from 314.2 N to 840.1 N at higher feed rates. The formation characteristics of the drill cap directly affect hole edge defects, with larger thickness and width leading to more pronounced burrs.